2007
DOI: 10.1210/en.2007-0701
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1: Distribution and Interaction with a G Protein-Coupled Receptor in the Rat Brain

Abstract: Nesfatin-1 is a recently identified satiety molecule detectable in neurons of the hypothalamus and nucleus of solitary tract (NTS). Immunohistochemical studies revealed nesfatin-1-immunoreactive (irNEF) cells in the Edinger-Westphal nucleus, dorsal motor nucleus of vagus, and caudal raphe nuclei of the rats, in addition to the hypothalamus and NTS reported in the initial study. Double-labeling immunohistochemistry showed that irNEF cells were vasopressin or oxytocin positive in the paraventricular and supraopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
255
1
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(304 citation statements)
references
References 38 publications
30
255
1
14
Order By: Relevance
“…Colchicine treatment was still helpful, as it reduced the number of immunopositive fibres that might otherwise mask the cells (see Figures 6g and h for comparison). Nesfatin-1/NUCB2 has previously been colocalised with serotonin in the caudal raphe nuclei, 9 and serotonincontaining neurons here are TRH positive. 20 Therefore, TRH, serotonin and nesfatin-1/NUCB2 are probably co-expressed in these nuclei.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Colchicine treatment was still helpful, as it reduced the number of immunopositive fibres that might otherwise mask the cells (see Figures 6g and h for comparison). Nesfatin-1/NUCB2 has previously been colocalised with serotonin in the caudal raphe nuclei, 9 and serotonincontaining neurons here are TRH positive. 20 Therefore, TRH, serotonin and nesfatin-1/NUCB2 are probably co-expressed in these nuclei.…”
Section: Discussionsupporting
confidence: 59%
“…Participation of nesfatin-1/NUCB2 in several autonomic functions is proposed, as nesfatin-1/NUCB2 neurons are present in high number in the hypothalamus and the lower brainstem autonomic centres. 9,33 Many of these neurons were activated by cold, suggesting that nesfatin-1/NUCB2 may mediate thermoregulatory, as well as other responses to cold. Regulation of heat loss and thermogenesis are the two main effectors to maintain body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest a role for central nesfatin-1 in the response to an immunological stressor. However, the release of central nesfatin-1 into the circulation has not been shown so far and several studies suggested local actions based on the restriction of the immunostaining to the axon and absence in dendrites [6,8,11,14]. In summary, these data point toward a peripheral source of nesfatin-1/NUCB2 measured in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…So far, only one study described the occurrence of mature nesfatin-1 peptide in the cerebrospinal fluid of rats, whereas in brain nuclei only full length NUCB2 was detected [24]. In all subsequent reports, only full length NUCB2 was detected by Western blot [8,27,36] or studies performing immunostaining did not distinguish between NUCB2 protein and nesfatin-1 peptide [5,6,8,10,13,14,16,18,25,32,34,42,43]. Since also full length NUCB2 exerts an anorexigenic effect it is also possible that this protein is the active circulating form.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, initial IHC analyses demonstrated the presence of NUCB2/nesfatin-1 protein in several hypothalamic nuclei, such as arcuate nucleus (ARC), paraventricular nucleus (PVN), supraoptic nucleus (SON), lateral hypothalamic area (LHA), and zona incerta, as well as in brainstem areas, such as the nucleus of the solitary tract (nucleus tractus solitarius, NTS), with pivotal roles in regulation of feeding (Oh et al 2006). These initial observations were later confirmed and extended, with the demonstration of NUCB2/nesfatin-1 mRNA and/or immunoreactivity in the above-mentioned hypothalamic and extrahypothalamic areas (Brailoiu et al 2007, Foo et al 2008, Kohno et al 2008. Of note, such detailed neuroanatomical Figure 1 Primary structure of NUCB2 protein, as precursor of nesfatin-1.…”
Section: Nesfatin-1 As Anorectic Molecule: Biological Effects and Neumentioning
confidence: 82%